Political ideology and international capital allocation - Kempf, Elisabeth; Luo, Mancy; Schäfer, Larissa; Tsoutsoura, Margarita (Journal of Financial Economics, 2023)
Does investors’ political ideology shape international capital allocation? We provide evidence from two settings—syndicated corporate loans and equity mutual funds—to show ideological alignment with foreign governments affects the cross-border capital allocation by U.S. institutional investors. Ideological alignment on both economic and social issues plays a role. Our empirical strategy ensures direct economic effects of foreign elections or government ties between countries are not driving the result. Ideological distance between countries also explains variation in bilateral investment. Combined, our findings imply ideological alignment is an important, omitted factor in models of international capital allocation.